Evaluation of the Serrated Lesions Detection Rate and Its Role as a Colonoscopy Quality Criteria - Clairet, Conceição de Maria Aquino Vieira; De Aquino, José Luis Braga; Clairet, Laurent Martial (Journal of Coloproctology, 2021)
Objectives To evaluate the serrated lesion detection rate in colonoscopy at a specialized clinic and its role as quality criteria for endoscopic examination.Methods This is an observational cross-sectional study with all patients that underwent colonoscopy between October 2018 and May 2019, performed by an experimented physician. A questionnaire was answered before the examination by the patient, and another questionnaire after the colonoscopy was answered by the medical team. All polyps identified were removed and sent to the same pathologist for analysis.Results A total of 1,000 colonoscopies were evaluated. The average age of the patients was 58.9 years old, and most of them were female (60.6%). In 62.5% of the procedures, polyps were removed, obtaining a total of 1,730 polyps, of which 529 were serrated lesions, being 272 sessile serrated lesions (SSL). This data resulted in a serrated lesion detection rate (SDR) of 29.2%, and of 14% when considering only the SSL detection rate (SSLDR). The right colon had higher rates, with 22.3% SDR and 15.3% SSLDR. Screening colonoscopies also presented a higher serrated detection rate, of 20%, followed by diagnostics and follow-up exams. Smoking was the only risk factor associated with higher serrated detection rate.Conclusions The serrated lesion detection rate is higher than the ones already previously suggested and the have the higher rates were stablished in the right colon and on screening exams.
Keywords: colonoscopy; colorectal cancer; polyps